The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3109/21691401.2016.1153485
|View full text |Cite
|
Sign up to set email alerts
|

Phages in modified alginate beads

Abstract: In order to increase stabilities and controlled/sustained released of T4 phages were encapsulated within alginate beads which were then coated with chitosan, polyethylene imine (PEI). Quite high loading capacities (over 90%) were achieved in these pH-sensitive microbeads. Coating with those polycations increased significantly stability both in "simulated gastric fluid" and bile salts especially in the case of PEI coating. The tests conducted in "simulated intestinal fluid" demonstrated that phages were release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 43 publications
2
33
1
Order By: Relevance
“…Sodium alginate-based matrices have been found suitable to incorporate different phages (Colom et al, 2017;Moghtader et al, 2017). In this work, similar titres of entrapped phages (Table 2) were obtained as compared to a previous work, which attests the efficiency of the entrapment strategy (Alves et al, 2018).…”
Section: Incorporation Of Phages And/or Cnma On Sodium-alginate Filmssupporting
confidence: 80%
See 1 more Smart Citation
“…Sodium alginate-based matrices have been found suitable to incorporate different phages (Colom et al, 2017;Moghtader et al, 2017). In this work, similar titres of entrapped phages (Table 2) were obtained as compared to a previous work, which attests the efficiency of the entrapment strategy (Alves et al, 2018).…”
Section: Incorporation Of Phages And/or Cnma On Sodium-alginate Filmssupporting
confidence: 80%
“…Most of encapsulation strategies reported for phages were driven by the need to protect them from the adverse conditions found in the digestive tract, such as the low pH and the activity of enzymes. In this context, phages have been encapsulated mostly in alginate-based microspheres (Abdelsattar, Abdelrahman, Dawoud, Connerton, & El-Shibiny, 2019;Colom et al, 2017;Moghtader, Eğri, & Piskin, 2017) and liposomes (Otero et al, 2019). More recently, studies have reported phages encapsulation to be further applied in food products.…”
Section: Introductionmentioning
confidence: 99%
“…as ion-exchange reaction would be taken place when the beads absorb bile salt (Li et al, 2011;Moghtader et al, 2017). Thus, this enhanced the mass transfer resistance and limits the penetration of bile salt into the beads (Obradović et al, 2015).…”
Section: Sgj Digestion Sij Digestionmentioning
confidence: 99%
“…As was shown by Międzybrodzki et al, only a small fraction (<0.1%) of oral administered phage was observed in the intestines, even after neutralizing antacid administration. The rationale behind several reviewed studies is to overcome such problems by protecting bacteriophages against harmful environments through embedding in a biomaterial matrix (Kim et al, 2015;Moghtader et al, 2017;Abdelsattar et al, 2019;Otero et al, 2019;Vinner et al, 2019).…”
Section: Advantages Of Bacteriophage Loaded Biomaterials For Local Dementioning
confidence: 99%